The Swedish Version of the Multidimensional Inventory for Religious/Spiritual Well-Being: First Results From Swedish Students - Wenzl, Magdalena; Fuchshuber, Jürgen; Podolin-Danner, Nikita; Silani, Giorgia; Unterrainer, Human-Friedrich (Frontiers in Psychology, 2021)
Background: Studies investigating the relationship between religiosity/spirituality and mental health have suggested both positive and negative associations, highlighting the importance of multifaceted assessment of these rather broad constructs. The present study aims at contributing to this field of research by providing a validated Swedish version of the Multidimensional Inventory for Religious/Spiritual Well-Being (MI-RSWB-S) and further examining how this instrument relates to Big Five personality factors, Sense of Coherence (SOC), and religiosity. Methods: Data were collected from a total of 1011 Swedish students (747 females; age range 18-40) via completion of an online survey, including a new Swedish Version of the MI-RSWB-S, the Ten Item Personality Inventory (TIPI), the Sense of Coherence Scale (SOC-13), and the Centrality of Religiosity Scale (CRS-5). Results: Results revealed adequate estimates of internal consistency and substantial evidence for the postulated six-dimensional structure. However, confirmatory factor analysis yielded poor fit indices, resulting in the development and validation of a revised measure of Religious/Spiritual Well-Being (RSWB), comprising the subscales General Religiosity and Connectedness. Most of the MI-RSWB-S dimensions were positively correlated with the personality domains Extraversion, Openness to Experience, Conscientiousness, and Agreeableness and negatively related to Neuroticism. SOC was positively linked to Hope Immanent, Forgiveness, Hope Transcendent, and Experiences of Sense of Meaning, whereas CRS exhibited positive correlations with all MI-RSWB-S subscales except Hope Transcendent. Conclusion: The findings of the current study support the validity and reliability of the Swedish adoption of the MI-RSWB and confirm previously reported associations with the Big Five personality traits, SOC, and CRS. More in general our results underline the putative substantial link between RSWB dimensions and mental health. Further research especially in clinical surroundings as well as by employing more representative samples is now warranted.